2021
DOI: 10.1002/asia.202100690
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Diphosphino‐Boryl PBP Pincer Backbone: PBP to POP Ligand Hydrolysis

Abstract: Since moisture may frequently be present in many solvents, it is important to know the reactivity of a catalyst against water for catalytic reactions. In order to explore the stability and understand the transformation process of diphosphino‐boryl‐based PBP pincer platform, [PdCl{B(NCH2PtBu2)2−o‐C6H4}] (1) was treated with PdCl2, HB(NCH2PPh2)2−o‐C6H4 was reacted with [PdCl2(cod)] (cod=cyclo‐octa‐1,5‐diene) and [Pd2(dba)3] (dba=dibenzylideneacetone), respectively, in the presence of water. Some novel palladium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…As mentioned above, water plays a critical role in the catalyst system, and the reaction cannot occur at lower temperatures. It was reported that PBP pincer complexes are unstable in the presence of water or alcohols especially at higher temperatures . The pincer backbone can be attacked by water or alcohol to generate other species or result in a decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, water plays a critical role in the catalyst system, and the reaction cannot occur at lower temperatures. It was reported that PBP pincer complexes are unstable in the presence of water or alcohols especially at higher temperatures . The pincer backbone can be attacked by water or alcohol to generate other species or result in a decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Pincer ligands have been widely used in transition metal-mediated catalysis due, in part, to their tunable steric and electronic properties. As part of the pincer ligand family, examples of bis­(phosphino)­boryl ligands ( R PBP) have been designed and synthesized by the Nozaki and Yamashita groups, and later, ( R PBP) ligands were studied with transition metals such as Os, Ir, Pt, Ru, Rh, Pd, and Co. Nickel complexes with t Bu PBP ligands have been isolated and reported to be active for olefin hydrogenation and CO 2 reduction. In addition, experimental evidence has been reported for the formation of a σ-borane (η 2 -B–H)­Ni­(0) species from the reaction of ( t Bu PBP)­NiH with 1,5-cyclooctadiene, which suggests that the hydride ligand is capable of migration from the Ni center to the boron center (Scheme ). Recently, the Nozaki group has synthesized a bidentate Ni(0) σ-borane complex {(η 2 -B–H/P)­Ni} and demonstrated its application in catalytic polymerization of ethylene for which the (η 2 -B–H/P)Ni complex behaves as a masked Ni­(II) boryl hydride that selectively produces linear polyethylene but not lower molecular weight ethylene oligomers (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…We are particularly interested in the structure, reactivity, and catalytic application of group 10 metal pincer complexes . In the present work, we surveyed crystallographic data from 130 group 10 metal pincer complexes supported by benzene-based PYCYP pincer ligands and performed theoretical computations for some selected complexes with the goal of obtaining information about the relationship among pincer platform substitution/composition, molecular structure, and thermodynamic stability.…”
Section: Introductionmentioning
confidence: 99%